A parsimonious destination loyalty model of Cox’s Bazar, Bangladesh - Quaddus, Mohammed; Shanka, Tekle; Hossain, Enayet (University of South Australia, 2011)
This paper has focused in developing a parsimonioustourism destination loyalty model based on theoretical andempiricalevidence. Information Processing Theory,Theory of Reasoned Action, and Theory of Planned Behaviour have been considered as ground for developing the model. Nine factors -perceived intrinsic cue, perceived destination brand image, perceived warranty, perceived price, perceived quality, perceived risk, perceived sacrifice, perceived satisfaction, and perceived destination loyalty - have been adopted to develop the model. To test the proposed model,data will be collected from the world’s longest sandy beach Cox’s Bazar,Bangladesh as a case application. The expected outcome of the study will contribute in enhancing the causal relationship among the factors, theoretically. Besides, these factors may be appeared as important in order to examine the structured destination loyalty model. This study will be helpful for destination operators and policy makers in formulating policies and business strategies. It will thus be supportive to improve present condition of tourism destination loyalty factors, particularly beach based destinations of Least Developed Countries (LDC’s) like Bangladesh.